Droplet lasers: a review of current progress. (10th April 2017) - McGloin, D
Abstract: It is perhaps surprising that something as fragile as a microscopic droplet could possibly form a laser. In this article we will review some of the underpinning physics as to how this might be possible, and then examine the state of the art in the field. The technology to create and manipulate droplets will be examined, as will the different classes of droplet lasers. We discuss the rapidly developing fields of droplet biolasers, liquid crystal laser droplets and explore how droplet lasers could give rise to new bio and chemical sensing and analysis. The challenges that droplet lasers face in becoming robust devices, either as sensors or as photonic components in the lab on chip devices, is assessed.